THE MEANING OF ENVIRONMENTAL BIOLOGY LEARNING: PERSPECTIVES OF SMPIT NATUNA INSAN QURANI STUDENTS - Vinni Helvionita Helvionita; M. Arif; Novia Dwi Wahyuni (Universitas PGRI Sumatera Barat, 2026)
This study aimed to explore the in-depth meaning of environmental biology learning from the perspective of SMPIT Natuna Insan Qurani students. Employing a qualitative descriptive phenomenological design, data were gathered through semi-structured in-depth interviews with 12 purposively selected Grade VIII and IX students, participatory classroom/field observations, and instructional documentation. Data analysis followed the Miles and Huberman interactive model encompassing data condensation, data display, and conclusion drawing/verification, supported by source and methodological triangulation. The findings reveal that students interpret environmental biology learning through four interconnected experiential dimensions: (1) cognitive comprehension of ecological interdependence and human-nature harmony; (2) direct affective relevance to daily life, particularly regarding waste reduction and marine ecosystem conservation; (3) behavioral transformation characterized by habitual pro-environmental actions (refusing single-use plastics and maintaining coastal cleanliness); and (4) deep contextual-spiritual internalization linking Natuna's archipelagic environment with Islamic ecological ethics (stewardship / khalīfah fī al-arḍ). Furthermore, students demonstrated a distinct preference for outdoor experiential learning over textbook-bound instruction. This study contributes to contextual science education theory and character education by showing how regional geographical authenticity and religious values synergize to transform abstract biology concepts into tangible ecological consciousness.